Perancangan ulang dan analisis desain UI/UX aplikasi identitas kependudukan digital (IKD) menggunakan metode design thinking - Mualfah, Desti; Mardiah, Adilla (Computer Science and Information Technology, 2024)
This research aims to increase user satisfaction of the Digital Population Identity (IKD) application by redesigning the user interface (UI/UX). The design features of the IKD application lack intuitiveness and have limited features, thus hindering people's interest in using the application. For this reason, a solution is needed to redesign the user interface (UI/UX) using the Design Thinking method and apply five design stages in the form of Design Thinking (Empathize, Define, Ideate, Prototype, and Testing), then this research produces a prototype of the IKD application. easier to use with test results using the System Usability Scale (SUS) showing that the prototype produced a score of 78, which is in the "GOOD" category, and shows that the redesigned IKD application meets user expectations in terms of ease of use and better experience